Mitigation of a prospective association between early language delay at toddlerhood and ADHD among bilingual preschoolers: Evidence from the GUSTO Cohort - GOH, Shaun K. Y. (Institutional Knowledge at Singapore Management University, 2020)
There is accumulating evidence of a prospective relation between early language problems and ADHD, a disorder associated with deficits in executive functioning. However, little is known regarding this link among bilingual children. Here, we investigate whether (i) the prediction from language to ADHD may be lower among bilinguals, and (ii) explore if this moderation can be explained by differential executive functioning ability. Utilising a prospective sample of 408 South-East Asian toddlers, bilingual exposure as a moderator of the link between language delay at 24 months to ADHD intermediate diagnosis at 54 months was first examined with an interaction model. Next, structural equation mediated moderation models examined if the proposed moderation could be explained by executive function measures of Snack Delay and Dimensional Change Card Sort (DCCS) task, when children were 41 months. Results indicate that higher levels of bilingual exposure moderated the prospective risk of language delay to ADHD diagnosis (Predominantly single-language exposed OR = 6.37; p = .011; Predominantly dual-language exposed OR = 0.30, p = .156). Thus, language delay associated with ADHD among toddlers predominantly exposed to one but not two languages. However, this could not be explained by differential executive functioning, as this moderation was not mediated by performance on Snack Delay or DCCS. Unexpectedly, bilingual exposure associated with ADHD among toddlers of typical language development. Possible explanations, including variation in the degree of social stigma and persistence of language delay between bilingual and monolingual children, and bilingualism as an additional cognitive load for ADHD, are discussed.